A High-Order Method for Weakly Compressible Flows (Communications in Computational Physics, 2017)
In this work, we introduce an IMEX discontinuous Galerkin solver for theweakly compressible isentropic Euler equations. The splitting needed for the IMEXtemporal integration is based on the recently introduced reference solution splitting [32,52], which makes use of the incompressible solution. We show that the overall method isasymptotic preserving. Numerical results show the performance of the algorithm whichis stable under a convective CFL condition and does not show any order degradation.